Electromagnetic fields theory of electrical machines - Part II: Uniqueness theorem for time-varying electromagnetic fields in hysteretic media - Mukerji, , SK; Goel, , SK; Bhooshan, , S; Basu,, KP (2005)
Conditions resulting in a unique solution of Maxwell's equations are investigated. For this purpose, time-varying electromagnetic fields in media exhibiting a linearized form of hysteresis are considered. The treatment is an extension of the uniqueness theorem for electromagnetic fields in hysteresis-free media. The major conclusions are that there is no initial condition for fields in lossy regions, however, boundary conditions must be satisfied for all values of time. The treatment presented may be useful to students preparing for a masters degree or final year bachelor's degree.